Effects of perinatal factors on body mass index and physical fitness of school-age children - Lučovnik, Miha (Zdravstveno varstvo, 2018)
Objective: To examine the effects of various maternal and neonatal perinatal factors on the child%s body mass index (BMI) and physical fitness at school-age. Methods: Data from two registries, the SLOfit database (a national surveillance system of children%s motor and physical development) and Slovenian National Perinatal Information System (NPIS) were analysed. Perinatal data for 2,929 children born in 2008 were linked to results of SLOfit testing of these children in 2016. Linear regression analysis was used to assess the potential relationship between several perinatal factors (very preterm birth, birth mass, maternal age, hypertensive disorders of pregnancy, gestational diabetes, parity, plurality, maternal pre-pregnancy BMI, mode of delivery, presentation, Apgar score at 5 minutes, and admission to a neonatal intensive care unit (NICU)) and child%s BMI or child%s physical fitness index (PFI) at the age of eight years. We also included child%s school grade and maternal educational level in the analysis. A p value <0.05 was considered statistically significant. Results: Children born to mothers with lower pre-pregnancy BMI and higher education had lower BMI and higher PFI (p<0.001) at school-age. Physical fitness was also inversely associated with nulliparity (p<0.001) and NICU admission (p=0.020). Conclusions: Among all perinatal factors studied, higher maternal education and lower pre-pregnancy BMI seem to be the most significant determinants of child%s BMI and physical fitness at school-age.
Keywords: body mass index; childbirth; debelost; gibalna učinkovitost; human pregnancy; indeks telesne mase; izobrazba matere; maternal education; nosečnost; physical fitness; porod; pre-pregnancy obesity; preterm birth